P-63 CHARACTERISTICS AND CLINICAL OUTCOMES IN CIRRHOTIC PATIENTS TREATED IN ICU BETWEEN 2018-2023 - Daniel Rojas Kozhakin; Juan Linares; Maria Rincon; Angelica Sanabria; Adriana Varon Puerta (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Cirrhosis is a chronic disease with a variable clinical course ranging from compensated stage to acute-on-chronic liver failure. The management of such patients focuses on multiorgan support in the intensive care unit (ICU). However, the criteria for defining the futility of management or even potential candidates for transplantation in our setting are not clearly established. Objectives: To describe the sociodemographic and clinical characteristics and outcomes of adult patients with liver cirrhosis treated in the ICU between 2018 and 2023 at the Cardioinfantil Foundation. Patients / Materials and Methods: A retrospective observational cohort study was conducted. Quantitative variables were described as mean and standard deviation or median and interquartile range, depending on their distribution. Qualitative variables were expressed as frequencies and percentages. To compare variables between groups, Student's t tests were used for continuous variables and chi-square tests or Fisher's exact test for categorical variables. Logistic regression models were applied to identify risk factors associated with mortality, adjusting for possible confounders. Results and Discussion: Statistically significant differences (p<0.001) were found associated with higher mortality in patients with higher CHILD, MELD and CLIF-C AD scores. Higher mortality was also found in patients with associated renal dysfunction, who developed any type of infection or who required IMV. No differences in survival were found in patients who underwent transplantation. Conclusions: Patients with cirrhosis treated in the ICU have a higher mortality rate in relation to greater renal dysfunction, need for IVM, impaired hepatic synthesis or the presence of any type of infection. Respiratory and urinary tract infection where the most common. No association was found with systemic inflammatory response and mortality. The proportion of suitable patients eligible for transplant was low. Prospective studies are required to identify the patient population that may benefit from early transplantation and thereby improve their survival.